An Essay on Economic Reforms and Social Change in China - Lindbeck, Assar (World Bank, Washington, DC, 2012)
The author applies a systems-oriented "holistic" approach to China's radical economic reforms during the past quarter of a century. He characterizes China's economic reforms in terms of a multidimensional classification of economic systems. When looking at the economic consequences of China's change of economic system, he deals with both the impressive growth performance and its economic costs. The author also studies the consequences of the economic reforms for the previous social arrangements in the country, which were tied to individual work units-agriculture communes, collective firms, and state-owned enterprises. He continues with the social development during the reform period, reflecting a complex mix of social advances, mainly in terms of poverty reduction, and regresses for large population groups in terms of income security and human services, such as education and, in particular, health care. Next, the author discusses China's future policy options in the social field, whereby he draws heavily on relevant experiences in industrial countries over the years. The future options are classified into three broad categories: policies influencing the level and distribution of factor income, income transfers including social insurance, and the provision of human services.